2010
DOI: 10.1007/s11274-010-0561-x
|View full text |Cite
|
Sign up to set email alerts
|

Production and characterization of chitosan obtained from Rhizopus oryzae grown on potato chip processing waste

Abstract: Potato chip processing waste of trimmed potato, potato peel and substandard (low-quality) potato chips, obtained from a potato chip processing plant, were used as substrates for chitosan production from Rhizopus oryzae. It was cultured on each waste product at 30 ± 2°C and 70% moisture content for 21 days. Fermented potato peel had the highest yield after 5 days of fermentation. The cultivation condition of chitosan obtained from R. oryzae was optimum for a peel size of less than 6 mesh, 70% moisture content a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…The fungal cells need an appropriate level of water in which to exercise the various biochemical reactions for the enzymatic breakdown and uptake of the biomass substrate. The results in this study indicated that M. rouxii ATCC 24905 was able to tolerate a lower substrate moisture content of 50% for growth and chitosan production in SS unlike other fungal strains previously studied for chitosan production via SSF, that were grown in 60% -70% moisture substrates [12] [22] [26]. Using less water to moisten the soybean meal substrate could mean less dilution of nutrients and growth factors due to water addition in the culture.…”
Section: Effect Of Incubation Periodmentioning
confidence: 89%
See 2 more Smart Citations
“…The fungal cells need an appropriate level of water in which to exercise the various biochemical reactions for the enzymatic breakdown and uptake of the biomass substrate. The results in this study indicated that M. rouxii ATCC 24905 was able to tolerate a lower substrate moisture content of 50% for growth and chitosan production in SS unlike other fungal strains previously studied for chitosan production via SSF, that were grown in 60% -70% moisture substrates [12] [22] [26]. Using less water to moisten the soybean meal substrate could mean less dilution of nutrients and growth factors due to water addition in the culture.…”
Section: Effect Of Incubation Periodmentioning
confidence: 89%
“…Fungal chitosan produced in the soybean residue cultures was extracted and isolated using an approach based on previously published methods [12] [22] [23]. The entire contents of each petri dish soy residues culture were processed first by extraction of residual proteins and other alkali soluble materials with NaOH solution with the desired concentration (1 M or 46% w/v) and volume-to-solids ratio (30:1 or 10:1, mL/g dry mass).…”
Section: Chitosan Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in order to reduce production costs, it has also been investigated the use of industrial residues as carbon source for fungi cultivation. It was reported in the literature the use of diverse agrofood by-products, namely glycerol from the biodiesel industry, 16 sugar cane molasses, 1 potato chip processing wastes 38 and yam bean wastes. 39 Many reports conclude that solid state fermentation is more efficient than submerged fermentation in fungal biomass production.…”
Section: Fungal Sources Of Chitinous Polymersmentioning
confidence: 99%
“…For example, potato wastes from the potato chip processing (rotten and substandard potato tubers, potato peel and substandard potato chips) were applied for the production of chitosan by fermentation with Rhizopus oryzae [115]. Enriched potato wastes from potato flakes processing (without pretreatment) were also found to be a good nutrient source for the production of glucoamylase by several strains of Aspergillus niger [116].…”
Section: Production Of Food Microorganisms Using Potato Pulp and Procmentioning
confidence: 99%